Desferrioxamine biosynthesis: diverse hydroxamate assembly by substrate-tolerant acyl transferase DesC. (23rd April 2018) - Ronan, Jade L.; Kadi, Nadia; McMahon, Stephen A.; Naismith, James H.; Alkhalaf, Lona M.; Challis, Gregory L.
Abstract : Hydroxamate groups play key roles in the biological function of diverse natural products. Important examples include trichostatin A, which inhibits histone deacetylases via coordination of the active site zinc(II) ion with a hydroxamate group, and the desferrioxamines, which use three hydroxamate groups to chelate ferric iron. Desferrioxamine biosynthesis in Streptomyces species involves the DesD-catalysed condensation of various N -acylated derivatives of N -hydroxycadaverine with two molecules of N -succinyl- N -hydroxycadaverine to form a range of linear and macrocyclic tris-hydroxamates. However, the mechanism for assembly of the various N -acyl- N -hydroxycadaverine substrates of DesD from N -hydroxycadaverine has until now been unclear. Here we show that the desC gene of Streptomyces coelicolor encodes the acyl transferase responsible for this process. DesC catalyses the N -acylation of N -hydroxycadaverine with acetyl, succinyl and myristoyl-CoA, accounting for the diverse array of desferrioxamines produced by S. coelicolor . The X-ray crystal structure of DesE, the ferrioxamine lipoprotein receptor, in complex with ferrioxamine B (which is derived from two units of N -succinyl- N -hydroxycadaverine and one of N -acetyl- N -hydroxycadaverine) was also determined. This showed that the acetyl group of ferrioxamine B is solvent exposed, suggesting that the corresponding acyl group in longer chain congeners can protrude from the binding pocket, providing insights into their likely function. This article is part of a discussion meeting issue 'Frontiers in epigenetic chemical biology'. This article is part of a discussion meeting issue 'Frontiers in epigenetic chemical biology'.